Progress on power swing blocking schemes and the impact of renewable energy on power swing characteristics: a review - Gunasegaran, M.K.; Tan, C.K.; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Illias, Hazlee Azil (Elsevier, 2015)
The occurrence of power swing had been reported to threaten the seamless operation of power system. Several cascaded outages and major blackouts in the world have been traced to mal-operation of distance relays due to power swing occurrences. As such, this paper will present a consolidated review on the power swing phenomenon, covering the causes of power swing, its impact to consumers and generators, as well as its detection and relay blocking schemes to prevent the mal-operation of distance relay. Given the wide arrays of power swing detection techniques and blocking schemes available up to date, particular attention is concentrated at the various power swing detection techniques on high voltage power system. In addition, the effect of modern renewable energy generations to the power swing characteristics is also presented in this paper. (C) 2015 Elsevier Ltd. All rights reserved.